An Update on Prenatal Diagnosis and Treatment of Congenital Adrenal Hyperplasia - New, Maria I.; Abraham, Moolamannil; Yuen, Tony; Lekarev, Oksana (Seminars in Reproductive Medicine, 2012)
Congenital adrenal hyperplasia causes genital ambiguity in females affected with the severe form of the disease; yet the abnormality is preventable with prenatal dexamethasone treatment that must be given to the mother before the ninth week of gestation. In the period from 1978 to March 2011 we have made prenatal diagnosis in 719 pregnancies. Our results indicate that the average Prader score of those fetuses treated with dexamethasone was 1.7, which is much lower than the average Prader score of 3.73 in those not treated. While our data demonstrate no significant abnormalities in the long-range medical and cognitive outcomes in patients prenatally treated with dexamethasone, the current protocol involves invasive procedures such as chorionic villus sampling or amniocentesis, and all fetuses are treated unnecessarily for several weeks before the sex and the affection status of the fetus is known. We are collaborating with Dr. Dennis Lo in Hong Kong to develop a noninvasive protocol, whereby at the sixth to seventh week of gestation we can determine the sex and the affection status of the fetus by harvesting fetal DNA from the maternal plasma. The method will eliminate invasive procedures and unnecessary prenatal treatment and bring noninvasive prenatal diagnosis to underdeveloped areas where amniocentesis and chorionic villus sampling are not available.
Keywords: congenital adrenal hyperplasia; prenatal treatment; genital ambiguity; noninvasive prenatal diagnosis; dexamethasone